The Importance of Acromegaloid Physical Features for Clinical Practice - Ivona Perić; Gordana Zamolo; Boris Bezak; Jasna Klen; Dubravka Jurišić-Eržen (Case Reports in Endocrinology)
Acromegaly and gigantism are hormonal disorders which develop as a consequence of chronic growth hormone hypersecretion. The prefix pseudo- is used to describe a certain clinical condition without a clearly proven characteristic of pathophysiological mechanism and basic biochemical features; pseudoacromegaly or acromegaloidism match the definition from above. In this case reports, we will try to provide a concise overview of diagnostic evaluation of acromegaloid physical appearance, while discussing two cases of patients who have similar clinical acromegaloid features as the first sign of the disease but have completely different etiologic backgrounds of their acromegalic appearance. The first case is of a 57-year-old male who presented with a marked acral growth and coarse facial features, but the diagnosis of secondary amyloidosis caused by multiple myeloma was confirmed just after biopsy of tongue and buccal mucosa. The second case is that of a 63-year-old male with an acromegaloid appearance caused by ectopic secretion of GH secreting lung carcinoma. The early diagnosis of ectopic acromegaly and pseudoacromegaly is still a challenging process. The key task is to confirm the GH axis abnormalities and establish the underlying disease, as a crucial step for faster treatment and need to avoid unnecessary therapeutic procedures to decreased mortality and improved quality of life.